ETR 300 : Alam Mewah Enterprise asas keusahawanan / Ms Farah Suwardi … [et al.] - Suwardi, Farah; Abdullah, Nor Hairani; Harun, Ms Norasiah; Razak, Intan Maysaraabd; Azib, Azliza (2000)
This Business Plan covered a whole important aspects in establish a business; as a background, objective for establish this company, administration aspects, marketing, operation, financial and whatever has been related with this business. There shown a several types of guide how to running the business as a tiles supplier.